SYNTHESIS AND CHARACTERIZATION OF ETHER-FUNCTIONALIZED IONIC LIQUIDS FOR BAMBOO DISSOLUTION BY USING SONOCHEMICAL METHOD - AB RAHIM, ASYRAF HANIM (2021)
Lignocellulosic biomass has emerged as an alternative source for chemicals and biofuel production to counter the heavy utilization of petroleum feedstock. Ionic liquids (ILs) have been widely used as solvents for dissolving lignocellulosic biomass during pretreatment due to their simple recyclability process. However, ILs normally have high viscosity which poses a limitation factor in ensuring maximum dissolution. Therefore, with the aim to improve the dissolution of lignocellulosic biomass in ILs, a series of ether- functionalized ILs were synthesized and characterized. The bamboo dissolution was conducted in the ether-functionalized ILs with dissolution periods from 10 to 60 minutes with 10 minutes intervals by using a direct probe ultrasonic method.